KDRT dalam Perspektif Maqashid Syariah - Catur Rohman Kusmayadi, Rudy; Umam, Khoirul (JURNAL PUSAKA: Media Kajian dan Pemikiran Islam, 2023)
This article identifies the forms or types of violence that occur in the household, where violence against a partner is very bad and threatens a household where harmony is the goal. Good communication can also avoid domestic violence and can even prevent the causes of divorce. The research method for this research is qualitative literature study, research data collection refers to Law Number 23 of 2004, previous research with a Maqashid Syariah perspective. Maqashid Syariah with the concept of protecting the five main principles in Islam, namely preserving religion, soul, mind, lineage and property. This is where the teachings of the Islamic religion and laws play a very important role in becoming a guide in running the household. Data from the Ministry of Women's Empowerment and Child Protection from January to July 2023 recorded that 18,250 cases of domestic violences occurred in Indonesia. This incident is truly ironic in Indonesia, where with a high level of religious belief there are still many perpetrators of violence. Through the Maqashid Syari'ah approach, it tries to find the causes and effects of problems that arise in domestic violence and the law tries to become a guideline so that it can be understood and implemented, in order to avoid and minimize the causes of cases of violence to establish a good and harmonious household life in accordance with the teachings Islam and can be sakinah mawaddah warahmah.